Housing bubble scars - Knut Are Aastveit; André Kallåk Anundsen; Bjørnar Karlsen Kivedal; Erling Røed Larsen (Norges Bank, 2024)
We study scar formation and persistence after a house price bubble has burst using data on 3,089 US counties and county equivalents over the period 1980q1-2019q4. We date house price booms and busts for each county, and identify periods with explosive house price developments. Applying a sharp bubble definition to the data, we observe the regularities that the probability of a housing bubble increases when housing supply is inelastic and when access to credit is easy. We differentiate between non-bubble price accelerations and bubble price accelerations, and demonstrate that there is scar formation after the latter. Conditioning on a set of factors, including county-fixed effects, our results show that house price reductions are larger and macro aggregate responses are stronger in areas in which there was a house price bubble. In particular, areas that experience a housing bubble burst are areas in which, subsequently, there are stronger and longer increases in unemployment and decreases in household income.
hdl:11250/3166774
Keywords: E32; E44; R30; C33; 330; Housing busts; Local housing cycles; Rational bubbles; Regional heterogeneity